Analysis of the principal's position in the implementation of quality management in education - Maju Siregar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The role of transformational principal leadership in developing educational quality principals can motivate teachers, students, and other stakeholders to work together to achieve quality improvement if they are able to articulate a strong vision, foster innovation in learning, and create an inclusive and collaborative school culture. This study aims to analyze the principal's leadership role in developing strategies and policies that support improving education quality, identify the barriers and challenges principals face in implementing programs to improve education quality, and examine the influence of principal leadership on teachers' participation and their involvement in efforts to improve education quality. A qualitative case study approach was used in this research. Interviews, observations, and analysis of related documents were used to collect data. The findings showed that principal leadership plays a very important role in developing strategies and policies that support educational quality improvement. Principals need to have a strong commitment and be able to formulate appropriate strategies to improve the quality of education in the school. In addition, principals are also faced with several barriers and challenges in the implementation of quality improvement programs, such as limited resources, resistance to change by some teachers, and lack of time. Principals need to manage resources effectively, establish effective communication with staff, and manage administrative tasks efficiently. The results also showed that principal leadership is associated with improved instruction.